Comments on 'Fair (t, n) threshold secret sharing scheme'. Issue 6 (1st November 2014) - Harn, Lein
Abstract : Tian et al . have proposed a fair ( t, n ) threshold secret sharing scheme recently. Three attacks have been introduced and analysed in this study. Among them, two attacks are associated with a synchronous network where the shares are released simultaneously, and one attack is associated with an asynchronous network where the shares are released asynchronously. In this study, the authors want to point out that the scheme only works properly in a synchronous network; but not in an asynchronous network. In other words, Theorem 3 in their paper which was associated with the attack in an asynchronous network is incorrect.